Perlindungan Hukum Hak Cipta Atas Cover Lagu Menggunakan Deepfake Voice Pada Platform Digital - Adena Fitri Puspita Sari; Adi Sulistiyono (Lembaga Pengembangan Kinerja Dosen, 2024)
This article aims to find out how copyright law protection can be done against song covers using deepfake voice. This research is a prespective normative legal research. The research approach uses statutory and conceptual approaches using primary legal materials, secondary legal materials, and tertiary legal materials. The technique of collecting legal materials uses literature study techniques. The technique of analyzing legal materials uses syllogism with a deductive mindset. Legal protection of copyright on song covers using deepfake voice uploaded on digital platforms can be done by providing protection of economic rights, moral rights, and sanctions. Therefore, to avoid copyright infringement, the perpetrators of song covers using deepfake voices uploaded on digital platforms need to pay attention to moral rights and economic rights regulated in Article 5 and Article 9 of the HC Law. The government is expected to make new regulations regarding the protection and supervision of deepfake voices in relation to the use of songs as well as adding digital platforms Article 3 paragraph (2) of PP No. 56 of 2021 concerning Management of Royalties for Copyright of Songs and/or Music